Post-Diagnostic Beta Blocker Use and Prognosis of Ovarian Cancer: A Systematic Review and Meta-Analysis of 11 Cohort Studies With 20,274 Patients - Wen, Zhao-Yan; Gao, Song; Gong, Ting-Ting; Jiang, Yu-Ting; Zhang, Jia-Yu; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Oncology, 2021)
Objectives: Previous experimental studies have indicated that exposure to beta blocker provides protective effects against ovarian cancer (OC). But, findings from epidemiologic studies have been still controversial. Therefore, we carried out a meta-analysis to update and quantify the correlation between post-diagnostic beta blocker usage and OC prognosis. Methods: The meta-analysis had been registered at PROSPEPO. The number of registration is CRD42020188806. A comprehensive search of available literatures in English prior to April 16, 2020 was conducted in PubMed, EMBASE, and the Web of Science databases. Random-effects models were used to calculate overall hazard ratios (HRs) and 95% confidence intervals (CIs). Publication bias assessments, and subgroup, sensitivity, and meta-regression analyses were also performed. Results: Of the 637 initially identified articles, 11 retrospective cohort studies with 20,274 OC patients were included. The summary HRs did not reveal any statistically significant associations between post-diagnostic beta blocker use and OC prognosis characteristics, such as total mortality (HR=1.08, 95%CI=0.92-1.27, I2=76.5%, n=9), cancer-specific mortality (HR=1.22, 95%CI=0.89-1.67, I2=88.1%, n=3), and progression-free survival (HR=0.88, 95%CI=0.75-1.05, I2=0, n=4). No evidence of publication bias was observed in current analysis. In our subgroup analyses, the majority of results were consistent with the main findings. However, several positive correlations were detected in studies with ≥800 cases (HR=1.20, 95%CI=1.05-1.37), no immortal time bias (HR=1.28, 95%CI=1.10-1.49), and adjustment for comorbidity (HR=1.20, 95%CI=1.05-1.37). Conclusions: Post-diagnostic beta blocker use has no statistical correlation with OC prognosis. More prospective cohort studies are necessary to further verify our results.